The Relationship Between Head Nurse Leadership Style and the Implementation of Cultural Safety by Nurses in Pediatric Care at H. Sahudin Kutacane Regional General Hospital - Yusnaini, Yusnaini; Ade Kartika; Nandara Priyanti Elna (Sean Institute, 2023)
Head nurses play a key role in creating a work environment that supports cultural safety. Transformational leadership enhances motivation, strengthens cross-cultural empathy, and fosters innovation in patient-centered care. This study aimed to analyze the relationship between the head nurse’s leadership style and the implementation of cultural safety by nurses in pediatric care. An analytical cross-sectional study was conducted using total sampling involving 45 pediatric ward nurses. Data were collected using the Multifactor Leadership Questionnaire (MLQ) Form 5X and a cultural safety assessment tool. Analysis was performed using the Chi-square test (α = 0.05). The results showed that most respondents were aged 26–35 years (53.3%), female (84.4%), held a Diploma in Nursing (62.2%), and had 1–5 years of work experience (40%). The predominant leadership style was transformational (46.7%). Cultural safety implementation was high (42.2%) and moderate (40.0%). A significant relationship was found between leadership style and cultural safety (p-value = 0.018). Transformational leadership was the most effective in enhancing cultural safety, with 66.7% of nurses under this leadership reporting a high level of cultural safety, compared to 56.3% moderate under transactional leadership and 62.5% low under laissez-faire. This study contributes to the development of nursing leadership models aimed at improving the implementation of cultural safety in Indonesia’s multicultural healthcare context.